2015
DOI: 10.15171/joddd.2015.049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Smoke on Salivary Total Antioxidant Capacity

Abstract: Background and aims. Cigarette smoke can induce oral cancer by its free radicals and oxidative damage. Salivary anti-oxidants system is believed to have an important role in defense mechanisms against oxidative stress. This study was compared total antioxidant capacity (TAoC) of saliva in smokers and nonsmokers.Materials and methods. In this cross-sectional study, 30 male smokers with mean age of 45.23 years and 30 nonsmokers with mean age of 45.30 years participated. Unstimulated whole saliva samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 15 publications
(14 reference statements)
2
32
1
3
Order By: Relevance
“…Bakhtiari et al confirmed that oxidative stress from smoking was not reduced even after using anti-oxidant drugs, including vitamin C (38). On the other hand, in an animal study, the activities of some antioxidant enzymes, including superoxide dismutase, catalase, and glutathione Int J High Risk Behav Addict.…”
Section: Discussionmentioning
confidence: 99%
“…Bakhtiari et al confirmed that oxidative stress from smoking was not reduced even after using anti-oxidant drugs, including vitamin C (38). On the other hand, in an animal study, the activities of some antioxidant enzymes, including superoxide dismutase, catalase, and glutathione Int J High Risk Behav Addict.…”
Section: Discussionmentioning
confidence: 99%
“…10 Cigarette smoke contains harmful components such as pyridine alkaloids, aromatic hydrocarbons and combustion gases; these can lead to the development of various life-threatening diseases. 15,16 Moreover, smoking has many side-effects which manifest in the oral mucosa, including delays in wound healing, periodontitis and premalignant and malignant oral lesions. 16 Due to the deleterious effects of smoking on the oral mucosa, associated salivary changes and the limited number of studies in this field, the aim of this study was to evaluate the salivary pH, BC and ALP activity of male smokers and healthy non-smokers in Hamadan, Iran.…”
mentioning
confidence: 99%
“…The participants were requested not to eat or drink two hours prior to saliva collection. The smokers were also prohibited from smoking for one hour prior to saliva collection [4]. To gather whole unstimulated saliva, the participants were asked to spit their saliva into 15 mL centrifuge tubes.…”
Section: Collection Of Saliva Samplesmentioning
confidence: 99%
“…There have been several studies that observed antioxidants level on human body, including in smokers. The total antioxidant capacity (TAoC) in smokers and non-smokers shower that TAoC in non-smokers was higher than that in smokers [4].…”
Section: Introductionmentioning
confidence: 96%